Gerakan Literasi Islamiyah Melalui Program Taklim dan Tarbiyah di Kecamatan Tiworo Tengah Kabupaten Muna Barat - Khaerul Aqbar; Muhammad Taufan Djafri; Ariesman Ariesman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2021)
The purpose of the Real Work Lecture (KKN) of STIBA Makassar Batch IV is to carry out community service as a pillar of “Tri Dharma Perguruan Tinggi”. The method of implementation of the service program begins by mapping the problems and needs of the community using SOAR Analysis. After the analysis is done, the work program is arranged according to the needs of the community. The successful work program was Taklim Qur'aniyah Virtual for Youth, Taklim Qur'aniyah Virtual for Mothers, Tarbiyah Qur'aniyah Virtual for Fathers. All these programs have shown significant initial results in accordance with the objectives of the KKN of STIBA Makassar that have been proclaimed, and will be continued by the Department of Dakwah and Cadreization of DPD Wahdah Islamiyah Muna Barat.